Anolis vicarius, new species, related to a. granuliceps (1986)
A single specimen of a small anole is described from the vicinity of Dabeiba, Antioquia, Colombia. It is provisionally regarded as related to A. granuliceps Roulenger but differs in smooth ventrals, larger dewlap and in pattern.  In 1981 JUAN MANUEL RENJIFO and VLADIMIR CORREDOR collected a single small anole along a trail near the rio Amparrado between the towns of Frontino and Dabeiba. Inmediately distinctive because of a bold shoulder ocellus, on close comparison it appeared to be related to Anolis qranuliceps Boulenger, known from the Choco of western Colombia down into northwestern Ecuador.  As the allopatric representative of the latter species it may be known as.